Tingkat Pengetahuan Konsumen di Apotek X Pabuaran Bojonggede, Kabupaten Bogor terhadap perilaku penggunaan Antibiotik - Khoirunnisa, Amalia; Teodhora, Teodhora; Djuhariah, Yayah Siti; Wulandari, Ainun (Program Studi S1 Farmasi, STIKES Senior, Medan, 2025)
Antibiotics are drugs used to treat or prevent bacterial infections. When used improperly, bacteria can adapt and develop resistance. Public awareness of appropriate antibiotic use plays a significant role in combating antibiotic resistance. To determine the relationship between antibiotic use behavior and the level of consumer knowledge at Jovita Pharmacy, Pabuaran, Bojonggede, Bogor Regency. This study employed a descriptive-analytic design with a cross-sectional approach. A total of 106 respondents who met the inclusion criteria were surveyed using a structured questionnaire. The data were analyzed using the Chi-Square test with a significance level of 0.05. Only 2.8% of respondents had good knowledge, and 33% demonstrated appropriate antibiotic use behavior. The Chi-Square test showed a significant correlation (p = 0.001) between knowledge and behavior in antibiotic use. There is a strong relationship between the level of knowledge and behavior in the use of antibiotics. Increased education and regulation are needed to promote rational use of antibiotics among the public.